2006
DOI: 10.1108/09526860610651708
|View full text |Cite
|
Sign up to set email alerts
|

Consumer evaluation of hospital foodservice quality: an empirical investigation

Abstract: Detailed information of the kind produced here is required for the formulation of managerial and sectoral policies to improve the quality of health and consumer nutrition care. The findings are noteworthy and, as far as the literature review showed, no previously published study has produced this level of detail on consumer preferences across foodservice attributes or their relationship to overall foodservice satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
3
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 29 publications
4
83
3
9
Order By: Relevance
“…In addition, the item 'I am satisfied with meal distribution time', which we introduced in the questionnaire, became part of the MSQ factor. Our questionnaire response rate was higher than those of other international studies (17,24,34) . Regarding use of the ACHFPSQ in the Italian context, we think that the questionnaire was well received by patients; this is also confirmed by the moderate/good response rate (72 %) compared with other studies (15,17,24,34) .…”
Section: Discussioncontrasting
confidence: 77%
“…In addition, the item 'I am satisfied with meal distribution time', which we introduced in the questionnaire, became part of the MSQ factor. Our questionnaire response rate was higher than those of other international studies (17,24,34) . Regarding use of the ACHFPSQ in the Italian context, we think that the questionnaire was well received by patients; this is also confirmed by the moderate/good response rate (72 %) compared with other studies (15,17,24,34) .…”
Section: Discussioncontrasting
confidence: 77%
“…Each hospital foodservice institution is unique and interventions must be customized to the specific patient population's needs and perceptions (Wright et al, 2006). The data pertaining to sensory evaluation of the diets (Table 3) indicate that the mean scores of freshness, taste, appearance and aroma of government hospitals were 2.93 ± 0.841, 2.55 ± 0.946, 2.68 ± 1.016 and 2.48 ± 0.873.…”
Section: IIImentioning
confidence: 99%
“…A thorough knowledge of the varied dimensions of hospital foodservice satisfaction is needed to understand patient expectations and promote the health and nutritional status of patients (Wright, Connelly, & Capra, 2006). Dubé et al (1994) found that food quality was the best predictor of patient satisfaction, followed by customization and attitude of the staff that deliver menus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution management of such prepared food is becoming a new challenge for supply chain managers. This also has background in the fact that the culinary quality of foodservice meals is a much debated issue throughout Europe [1][2][3] and the consumption of prepared meals is growing and will continue to grow in the foreseeable future, due to trends in demography and life-style (more elderly people, more one-person households in the future, and more out-of-home dining) [4]. This paper studies the supply chain for professionally prepared meals, in which a new innovative concept for producing and distributing the main components is applied.…”
Section: Introductionmentioning
confidence: 99%